Improved Power Flow Algorithm for Distributed Ring Network Based on Loop Analysis - Si GU; Xiao SUN; Chang MA; Jing CHEN (发电技术)
In order to improve the ability of clean energy consumption and the reliability of power supply, distribution network operation is attracting more and more attention. In view of the non-convergence of the traditional forward and backward substitution method, an improved power flow algorithm for distribution network with ring network was proposed by combining the loop analysis method with the forward and backward generation power flow algorithm. The branch current was decomposed to compensate the split-point current, and the non-convergence phenomenon was changed. The validity and accuracy of the algorithm were verified by data simulation with Matlab.